CTNI-05. MOLECULAR ANALYSIS OF THE PHASE I D-TERMINED TRIAL ON CONCURRENT AND ADJUVANT TEMOZOLOMIDE WITH MINOCYCLINE IN NEWLY DIAGNOSED HIGH-GRADE GLIOMA. (14th November 2022) - McKean, William; Boucher, Kenneth; Yang, Jingye; Sonty, Karthik; Jensen, Randy; Shrieve, Dennis; Salzman, Karen; Johnson, Brett; Thomas, Melissa; Moss, Whitney; Behunin, Amanda; Prystas, Elizabeth; et al.
Abstract: BACKGROUND: Minocycline blocks microglial TNF signaling and downstream NF-κB activation, which reduces the mesenchymal phenotype in preclinical models of GBM. Primary analysis of the D-TERMINED trial identified a maximal tolerated dose (MTD) of oral minocycline at 150 mg BID in combination with temozolomide and radiation. In the overall population, the secondary objective of improved PFS was not met. Here, response is further stratified by biomarkers delineating mesenchymal subtype (OLIG2, CD44), microglial activation (IBA-1), and NF-κB signaling (P-p65). METHODS: Patients with newly diagnosed high-grade glioma received continuous oral minocycline during concurrent chemoradiation and adjuvant temozolomide. Twenty patients were included in the MTD efficacy population. Within this cohort, immunohistochemistry for OLIG2, CD44, IBA-1, and P-p65 was performed on nineteen patient tumor samples. For each biomarker, the mean percent positivity or number/HPF was compared between patients who exceeded or did not exceed expected PFS. Spearman correlation coefficients were also generated for pairwise comparison of these biomarkers. RESULTS: In patients with high PFS, 12.7% of tumor cells were positive for OLIG-2, 36.5% for CD44, and 23.9% for P-p65, with 41.7 cells/HPF positive for IBA-1. Comparatively, in patients with low PFS, 9.4% of tumor cells were positive for OLIG-2 (p = 0.59), 34.1% for CD44 (p = 0.77), and 22.3% for P-p65 (p = 0.85), with 31.1 cells/HPF positive for IBA-1 per HPF (p = 0.38). The only biomarkers demonstrating significant relationship were P-p65 and IBA-1, with a rank correlation of 0.637 (p = 0.007). CONCLUSIONS: Exploratory analysis of D-TERMINED concludes that OLIG-2, CD44, IBA-1, and P-p65 are not predictive of improved PFS within high-grade glioma patients treated with SOC and minocycline. Concurrent use of minocycline with chemoradiation is therefore not indicated in these or unselected populations. Significant correlation is seen between IBA-1 and P-p65, biomarkers of microglial activation and NF-κB signaling. SPONSORSHIP: Funding provided by the Musella Foundation and NIH grant P30CA042014.